The Effect Of Transfer Pricing, Audit Quality, And Profitability On Tax Avoidance In Energy Sector Companies Listed On The Indonesia Stock Exchange - CORNELLIA, Tabitha Deisy; SONDAKH, Jullie J.; WEKU, Priscilia (PT Keberlanjutan Strategis Indonesia, 2023)
The tax sector is the biggest major contributor to state revenue and an important component in the State Budget. Taxes which are mandatory levies to the state owed by corporate and individual taxpayers, without any benefits that can be shown directly, make taxes a burden for corporate or individual taxpayers. Which its causes a conflict of interest between the government who wants huge tax revenues and companies who want small tax payments. Therefore the company takes action to carry out a tax avoidance strategy by minimizing high tax payments. This study aims to determine the effect of transfer pricing, audit quality and profitability on tax avoidance in energy sector companies on the Indonesia Stock Exchange for the 2018-2021 period. The data source used in this study is secondary data taken from the official website of the Indonesia Stock Exchange. The sample in this study used purposive sampling method, and there are 23 sample companies selected from 79 companies. The results showed that transfer pricing had an significant effect on tax avoidance, audit quality did not effect on tax avoidance, and profitability had an significant effect on tax avoidance.